A multicast delivery scheme for VCR operations in a large VOD system - Jung-Min Choi; Seung-Won Lee; Ki-Dong Chung (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Multicast transmission is one of the solutions to reduce the cost in large VOD systems. However, it is difficult to implement the interactive operations for an individual user in a multicast transmission system. We propose a frame based multicast transmission scheme to serve a large number of users and reduce additional channels while supporting VCR operations. This scheme supports both normal playback and VCR playback via the identical channels. The proposed FBMT is to deliver frames via appropriate channels based on frame type (I, P, B) of MPEG video. FBMT has superior performance over the multicast systems in terms of both initial blocking probabilities and VCR blocking probability. The initial blocking probability of the FBMT is decreased as the arrival rate is increased further, VCR blocking probability is always 0% to admitted users.